Life Cycle Assessment of Natural Gas Production in Java Sea-East Java Province, Indonesia - Chairani, Ellyna; Saleh, Errik; Hanifah, Novi; Aman Santosa, Adrian; Putri Ayu, Anita; Andreina, Richa (Mutiara: Multidiciplinary Scientifict Journal, 2024)
Energy products including natural gas play a very important role in the context of global economic, industrial, and infrastructure development. However, it is undeniable that the production process from raw material extraction to ready-to-use products has an impact on the environment. This study was conducted to evaluate the environmental impact of natural gas production in the Kepodang field, East Java Province, Indonesia. The next objective is to analyze the magnitude and significance of the impact or hotspot analysis. The characterization results for 4 main categories show: Global Warming Potential 70.02 kg CO₂ eq, Ozone Layer Depletion 1.11E-06 kg CFC-11 eq, Acidification Potential 0.65 mol H+ eq, Marine Eutrophication 0.30 kg N eq, and Freshwater Eutrophication 2.17E-03kg P eq. The results also show that throughout the life cycle of this product, the largest contributor to environmental impacts is in the downstream phase, especially the user gas metering unit process. This is due to the 200 km of pipelines for product transportation from the Central Processing Platform (CPP) to the user gate. Pipeline parameters (Ecoinvent database) refer to long-distance pipelines with high capacity. In addition, hotspots were also identified in the core phase: gas measurement and chromatography, gas turbine generators, and flare gas.